P071 Cost efficacy savings on serological follow up for syphilis at an urban sexual health clinic. (30th June 2016) - Gilson, Rebecca
Abstract : Background/introduction: General Practitioners (GPs) in Lothian are requesting syphilis serology in 65% of individuals being tested for HIV. Adding syphilis to the remaining 35% would cost around £7000. In Edinburgh full serology (IgG, RPR, TPPA, IgM) is performed in all with a previous syphilis diagnosis. HIV positive individuals are tested 6 monthly. BASHH 2015 Syphilis Guidelines recommend RPR follow up and annual monitoring in HIV positive individuals. The aim was to evaluate if full serological screening was appropriate and whether cost savings could be made. Methods: One hundred individuals with full serological testing for syphilis, 30/9/15 to 29/10/15. Age, risk group, HIV status, stage of infection, PCR, treatment, symptoms, follow up and infection risks were collated. Results: 88 male, 12 female. Twenty one early infection (all positive RPR), 4 re infection (all rise in RPR), 7 late latent and 54 treated infection. Forty seven HIV positive. Of these 14 (21%) had no ongoing risks and 16 (34%) had ongoing risks, longstanding RPR 0. Forty HIV negative. Twenty four (60%) were MSM with treated STS, and a longstanding RPR 0. Recommendations: Testing should be annual RPR in HIV positive individuals with no ongoing risks. In those with ongoing risks RPR alone sufficient for monitoring. All with re infection would have been picked up on RPR. In HIV negative individuals, most had ongoing risks but a longstanding RPR 0. Monitoring with RPR only would have diagnosed all re infections. Discussion: It was difficult to vary testing based on risk assessment and concerns that RPR only may miss prozone. However, there was agreement that IgM should no longer be performed. At £3.77/test approximately £377/month would be saved in this group alone. This would apply to all other testing with considerable cost savings